Decaying beauty - Paras, Keith G. (2010)
The dilemma presented by "Art Beautiful" is the subject of my works in this study. To solicit the viewers' reaction in the painting and, at the same time, to evoke the feeling of regret are the main goals of my paintings. The concept of degradation of the environment is translated into defilement of painting adding dirt on the image, metaphoric of pollution.
"March 2010"
Thesis (BFA)--University of the Philippines Diliman
Keywords: Paintings